Diffuse cutaneous bullous mastocytosis in a newborn. Issue 2 (3rd April 2013) - Wawrzycki, Bartłomiej; Pietrzak, Aldona; Chodorowska, Grażyna; Kanitakis, Jean
Abstract Diffuse cutaneous mastocytosis is the rarest subtype of mastocytosis among those that affect children. A 7‐month‐old girl presented at birth dry and thickened skin. On the second day of life, tense blisters appeared on erythrodermic areas and during the next days spread over the face, trunk, and limbs. The skin was bright red, had a "peau d'orange" appearance, and was considerably thickened with numerous translucent and hemorrhagic blisters. A skin biopsy revealed massive infiltration of the dermis with mast cells, leading to the diagnosis of diffuse erythrodermic mastocytosis. Systemic corticosteroids were given along with antihistamines with good results. Despite the progresses in the understanding of pathogenesis, genetics, and diagnostic criteria of mastocytosis, clear and reliable prognostic markers are still lacking, especially in order to predict systemic involvement. not only in diffuse but also in the commoner forms of the disease.